ENHANCING THE LEGAL PROFESSION’S CAPACITY FOR INNOVATION: THE PROMISE OF REFLECTIVE PRACTICE AND ACTION RESEARCH FOR INCREASING ACCESS TO JUSTICE - Leering, Michele M. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
Recent national reports have documented growing justice gaps in Canada and have identified a compelling need for innovation in the justice sector to better meet the needs of the public. Nurturing a greater capacity for individual, collective, and critical reflection will ensure the legal profession is much better equipped to respond creatively and strategically to a lack of equal access to justice. In this article, I explore the generative and transformative potential of reflective practice – an important professional competency in other professional disciplines, but under-theorized in law, and action research – a dynamic and flexible form of qualitative research for supporting a culture of innovation in the legal profession and the justice system. Reflective capacity is a crucial enabler of innovative thinking, and it undergirds approaches to encouraging individual and systems change emerging from the organizational learning and innovation literature. An enhanced capacity for reflection will also support more generative and “future-forming” dialogues within the profession and between justice system stakeholders. Furthermore, systematically reflecting on disorienting empirical data about the troubling state of access to justice could develop an “access to justice consciousness” in law students and legal professionals, leading to a stronger willingness to take action to narrow the justice gaps. Introducing action research as an unpretentious and effective enabler of profound transformation and innovation in individual and organizational practices offers significant promise for tackling the “wicked problem” of access to justice. Practical illustrations of action research as an enabler of innovation drawn from legal practice are provided.